(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This study is on assessment of transient vibration of a rocking structure on two-parameter uplifting foundation model. This foundation model, Filonenko-Borodich (F-B) considers effect of continuity and interactions of the structure with the surrounding foundation surface. The foundation model aids uplift because of its elastic and flexible nature. During ground movement, some forces are generated which cause foundation to vibrate, rock and sometimes uplift due to increasing upward forces and then leading to reduction in the spring stiffness and increase in soil flexibility. This sometimes causes upward trend in the structural response which might affect structural integrity and stability. The use of damping and its effects on the structure response considering uplift are evaluated for a structure on two-parameter foundation. Equations describing the motion were developed by summing forces acting on the structure and foundation, considering equilibrium of moments for the conditions of before uplift and during uplift of the system in accordance using Newton’s second law of motion, D’Alembert’s principles. The resulting equations were solved by applying them in Duhamel Integral form and Simpson’s method used for the numerical solution for the structure responses. The result showed an upward trend in the structural responses during uplifting hence uplift of building foundation is not always beneficial.